TI_GERICHTE 14.2021.24 vom 1. April 2021 , Fallimento senza preventiva esecuzione. Sospensione dei pagamenti - TI Tribunale d'appello (2021)
Fallimento senza preventiva esecuzione. Sospensione dei pagamenti